Gender bias in bangladesh civil service: a case study from 12 different cadres (Bangladesh Journal of Public Administration, 2022)
This study attempts to identify the core reasons for gender bias in the Bangladesh Civil Service. The purpose is to learn about the current state of such bias and whether and to what extent women civil servants are impacted by it, as well as its consequences in terms of career growth. For this study, the researcher employed qualitative methodologies, relying mainly on primary data acquired through a questionnaire survey of 111 civil servants. Results demonstrate that in the civil service, women are subjected to a greater degree of gender bias than males, followed by the third gender. It also shows that social attitudes and lack of child care facilities are two of the key reasons for such bias and gender stereotyping, underrepresentation of women, the existing gender gap, insufficient paid maternity leaves, biased rules, and a lack of awareness might be regarded as minor sources of gender bias in this sector.  Gender bias has a significant impact on postings, leadership positions, major project assignments, and challenging roles, as well as a moderate impact on other variables such as promotion, recognition for equal work, performance review, obtaining mentors and training opportunities, compensation and awards, recommendations, and recruiting, according to the data.